2019
DOI: 10.4269/ajtmh.18-0922
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni Infection as a Predictor of Low Aerobic Capacity in Ugandan Children

Abstract: Using the 20-meter shuttle run test (20mSRT) as a morbidity metric, we assessed whether Schistosoma mansoni infection was associated with decreased aerobic capacity in Ugandan children across a range of altitudes, either at low (∼600 m) or high (∼1,000 m) altitudes. A total of 305 children were recruited from six schools within the Buliisa District, Lake Albert, Uganda. A subset (n = 96) of these had been previously assessed and treated for schistosomiasis ± malaria 2 weeks prior. Fitness scores on the 20mSRT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
8
1
Order By: Relevance
“…The two studies published on the plateau area report inconsistent findings. Smith et al [ 67 ] showed aerobic endurance increases at high altitude (600–1,000 m); however, their altitude range is much lower than our study. In contrast, Chen [ 68 ] found that, at altitudes (3,417–4,300 m) similar to the present study, maximum oxygen uptake was inversely correlated with altitude in children and adolescents.…”
Section: Discussioncontrasting
confidence: 87%
“…The two studies published on the plateau area report inconsistent findings. Smith et al [ 67 ] showed aerobic endurance increases at high altitude (600–1,000 m); however, their altitude range is much lower than our study. In contrast, Chen [ 68 ] found that, at altitudes (3,417–4,300 m) similar to the present study, maximum oxygen uptake was inversely correlated with altitude in children and adolescents.…”
Section: Discussioncontrasting
confidence: 87%
“…To do so, we recommend a combination of both rapid urine and faecal sampling methods with inspection of a more extensive range of point-of-contact morbidity markers to provide a better insight into individual disease progression(s) [24]. Future use of 20 m shuttle-run tests to assess children's aerobic capacity in relation to S. mansoni infection could be insightful, as recently shown elsewhere [25]. However, with coronavirus disease 2019 (COVID- 19) suspending annual MDA, we should expect and better prepare for increasing severity of intestinal schistosomiasis in following years.…”
Section: Discussionmentioning
confidence: 88%
“…To do so, we recommend a combination of both rapid urine and faecal sampling methods with inspection of a more extensive range of point-of-contact morbidity markers to provide a better insight into individual disease progression(s) [24]. Future use of 20 m shuttle-run tests to assess children's aerobic capacity in relation to S. mansoni infection could be insightful, as recently shown elsewhere [25]. However, with coronavirus disease 2019 (COVID-19) suspending annual MDA, we should expect and better prepare for increasing severity of intestinal schistosomiasis in following years.…”
Section: Discussionmentioning
confidence: 88%